2007
DOI: 10.3758/bf03193501
|View full text |Cite
|
Sign up to set email alerts
|

The effects of processing time and processing rate on forgetting in working memory: Testing four models of the complex span paradigm

Abstract: Four models of working memory processes in the complex span paradigm were tested: The task-switching model of Towse, Hitch, and Hutton (1998), the interference account of Saito and Miyake (2004), and two versions of the time-based resource-sharing model of Barrouillet, Bernardin, and Camos (2004). On the basis of a reading span paradigm that used segmented sentences, the effect of processing time on the recall of words was investigated while the amount of processing was held constant. Two conditions of reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
118
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 29 publications
1
118
2
2
Order By: Relevance
“…Bernardin, & Camos, 2004;Barrouillet, Bernardin, Portrat, Vergauwe, & Camos, 2007;Barrouillet, Portrat, & Camos, 2011;Camos & Portrat, 2015;Hudjetz & Oberauer, 2007;Ricker & Cowan, 2010;Vergauwe, Barrouillet, & Camos, 2009; but see Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012;Oberauer & Lewandowsky, 2013), and (2) increasing the number of times a memory item has been refreshed, by presenting cues prompting participants to think of specific WM items during a retention interval, results in better memory performance for that item (Souza, Rerko, & Oberauer, 2015). In these studies, researchers have focused on the effects of refreshing on memory performance at the end of the trial or at the end of the experimental session.…”
mentioning
confidence: 99%
“…Bernardin, & Camos, 2004;Barrouillet, Bernardin, Portrat, Vergauwe, & Camos, 2007;Barrouillet, Portrat, & Camos, 2011;Camos & Portrat, 2015;Hudjetz & Oberauer, 2007;Ricker & Cowan, 2010;Vergauwe, Barrouillet, & Camos, 2009; but see Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012;Oberauer & Lewandowsky, 2013), and (2) increasing the number of times a memory item has been refreshed, by presenting cues prompting participants to think of specific WM items during a retention interval, results in better memory performance for that item (Souza, Rerko, & Oberauer, 2015). In these studies, researchers have focused on the effects of refreshing on memory performance at the end of the trial or at the end of the experimental session.…”
mentioning
confidence: 99%
“…The first mechanism is distraction of attention. The processing demand is assumed to distract a general attentional mechanism-sometimes referred to as a bottleneck-from the memory items, thereby preventing their maintenance or further consolidation in memory (Barrouillet et al, 2004;Hudjetz & Oberauer, 2007). The size of the distracting effect should depend on the proportion of time the processing task occupies attention, but not on the material used in the processing task.…”
mentioning
confidence: 99%
“…4 Indeed, rehearsal may well be completely impossible during verbal processing of the form employed here, where each successive processing operation follows on directly from the completion of the previous one (Hudjetz & Oberauer, 2007). Given this, one might question why verbal processing does not lead to a greater degree of forgetting than currently observed.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, refreshment is assumed to operate more rapidly than subvocal rehearsal as it need not involve the retrieval of the full phonological form of the memoranda (Barrouillet et al, 2007;Cowan et al, 1998;Hudjetz & Oberauer, 2007;Raye, Johnson, Mitchell, Reeder, & Greene, 2002). A number of authors have suggested that refreshment operates only on the most recently presented item (Raye et al, 2002;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation